A Service-Based Program Evaluation Platform for Enhancing Student Engagement in Assignments - Wu, Ye-Chi; Ma, Lee Wei; Jiau, Hewijin Christine (Educational Technology ＆ Society, 2013)
Programming assignments are commonly used in computer science education to encourage students to practice target concepts and evaluate their learning status. Ensuring students are engaged in such assignments is critical in attracting and retaining students. To this end, WebHat, a service-based program evaluation platform, is introduced in this work to support programming assignment practice. WebHat provides students with immediate assistance via online evaluation services and helps teaching staff monitor student status and progress. Based on the results of this system, teaching staff can dynamically adjust, if necessary, online evaluation services to provide further help to enhance student engagement in the ongoing assignment. To demonstrate the effectiveness of WebHat, an empirical study is conducted with freshman students as the subjects during the Introduction to Computer Science course. The results show that students are encouraged to start working on their assignments earlier and develop programs in the desired direction with the aid of the dynamically adjusted online evaluation services. WebHat thus enables students to submit better final products with regard to both functionality and quality.